Pattern of Tuber melanosporum extramatrical mycelium expansion over a 20-year chronosequence in Quercus ilex-truffle orchards (MYCORRHIZA, 2014)
Successful cultivation of black truffle (Tuber melanosporum) requires a long-term investment and the maintenance of the symbiosis throughout its preproductive and productive years. Monitoring the symbiosis over time is challenging, as it requires methods that can detect the belowground proliferation of the fungus associated with its host tree. In this study, we used a chronosequence design to study the expansion pattern of this fungus as the host tree grows. We hypothesize that this expansion can be estimated by monitoring T. melanosporum DNA from soil beneath host trees of different ages (3, 5, 7, 10, 14, and 20 years old) and at different distances from the trunk of the trees (40, 100, and 200 cm). We also wished to evaluate the presences of Tuber brumale and Tuber indicum, potentially problematic truffle species, in these plantations. To detect the mycelium of T. melanosporum in these soils, we extracted DNA and performed polymerase chain reaction (PCR) with Tuber species-specific primers, and to estimate DNA amount, we measured relative band intensities from the amplicons in agarose gels. Both age and distance were related to T. melanosporum DNA quantity, which was more abundant in the oldest age classes, reaching a plateau in 5-7 years. At 40 cm from the tree, there were no differences in T. melanosporum DNA amounts in orchards of different ages, but at 100 and 200 cm, younger orchards had less T. melanosporum DNA. We did not detect DNA from T. brumale or T. indicum in any of our samples.
The following values have no corresponding Zotero field: pub-location: 233 SPRING ST, NEW YORK, NY 10013 USA publisher: SPRINGER

Weed management and irrigation are key treatments in emerging black truffle (Tuber melanosporum) cultivation - Olivera, a; Fischer, C. R.; Bonet, J. a; Martínez de Aragón, J.; Oliach, D.; Colinas, C. (New Forests, 2011)
Interest in conversion of marginal agricultural lands to small oak woodlands for the production of black trufﬂes (Tuber melanosporum Vittad.) is increasing in the native black trufﬂe areas of France, Spain and Italy as well as suitable or amended sites throughout the world due to high economic returns for gastronomically valuable trufﬂes. Successful long-term management of a perennial plantation replacing an annual crop requires understanding the system in all phases of the life cycle, and in the case of trufﬂes this involves understanding the interactive growth of the aboveground host and the belowground symbiotic ectomycorrhizal fungus whose fruitbody is the desired trufﬂe. Here we focus on the pre-production phase, 4 years after establishing the trufﬂe-oak plantation and prior to trufﬂe production. We tested the inﬂuence of weed control, irrigation and fertilizer, each at 3 levels, on plant growth and ectomycorrhizal proliferation in three trufﬂe-oaks plantations in northeast Spain. Results show that adequate weed control improves root and shoot dry weight while fertilizer and irrigation treatments did not inﬂuence plant growth. The low dose of irrigation (50% of the estimated water deﬁcit for the site) and glyphosate weed control both increased total root tips/plant and T. melanosporum colonized tips (ectomycorrhizae) by approximately two-fold, compared to control treatments. Distribution of the ectomycorrhizae within the soil proﬁle was signiﬁcantly inﬂuenced by the low dose irrigation treatment, with increases observed in the 10–20 cm and the 20–30 cm deep layers compared to the control and high irrigation treatments. Four years after planting, T. melanosporum remained the dominant fungal symbiont, despite the presence of 14 other ectomycorrhizal morphotypes from these sites.
Keywords: Ectomycorrhizae; Holm oak management; Quercus ilex; Root tips; Trufﬂe-oaks

Cultivation of black truffle to promote reforestation and land-use stability - Bonet, J. A.; Fischer, C. R.; Colinas, C. (Agron. Sustain. Dev., 2006)
Cultivation of black truffle, Tuber melanosporum Vitt., has become an important agricultural alternative in rural Mediterranean regions due to its success in relatively harsh conditions, its high market value and diminishing production in natural areas. In addition, truffle cultivation requires relatively low agricultural inputs, promotes reforestation and economic restoration of rural lands and land-use stability. However, there remain major issues regarding the management practices to ensure successful black truffle production. We therefore conducted an experiment to evaluate 3 levels of irrigation based on monthly water deficit and the effects of currently applied weed control systems and fertilization. Treatment effects were evaluated by examining the mycorrhizal status of out-planted 1-yr-old Quercus ilex L. seedlings and seedling growth parameters after 18 months in 3 distinct experimental truffle plantations located in the foothills of the Spanish Pyrenees. We found that replacing one-half of the water deficit of the driest month (moderate irrigation) promoted the proliferation of T. melanosporum mycorrhizae, while high irrigation reduced fine root production and truffle mycorrhizae. Glyphosate weed control improved seedling survival by up to 16% over control seedlings without jeopardizing truffle mycorrhizae in the first year. Fertilization did not improve seedling growth or influence its mycorrhizal status. We describe the persistent relationship between this ectomycorrhizal fungus and Q. ilex by quantifying old and new mycorrhizae and we discuss the ecological implications of the symbiosis
Keywords: agricultural alternative; ectomycorrhiza; Quercus ilex; water deficit